A semiotic reading of fashion advertisements in the lifestyle format - Sarmiento, Maria Alicia Aquino (College of Home Economics, University of the Philippines, 2009)
Fashion advertising heavily exploits brand imaging by marketing illusions rather than commodities. This study aimed to deconstruct selected fashion advertisements in the lifestyle format,a format that depicts a personality, product, and setting, all engaged in an activity. While promoting specific fashion and apparel products, the lifestyle format also circulates meanings about class, privilege and status. Five storefront displays were selected based on set criteria. These were analyzed within the framework of semiotics, deriving the denotations and connotations of the signifies in these images. Drawn from this deconstructionism was the social function served by these advertisements through the circulation of meanings about class, privilege, and status. The images in these advertisements not only advertise brands and products but manipulate consumers towards higher standards of living. However, while the advantages of consuming luxury products are always clearly represented, these products are still shown in the real world settings in order to attract broader markets, despite the fact that the products being advertised are rendered exclusive based on their prices alone. Because of fashion's inextricable ties to culture, understanding the frameworks that operate in culture is crucial; to furthering professional and academic expertise on fashion.